Thickness of the ventricles and interventricular septum in men and women of the mesomorphic body type with normal body mass index according to echocardiography - L. P. Martirosyan; I. A. Balandina (Сибирский научный медицинский журнал, 2020)
The aim of the study was to establish the thickness of the ventricles and interventricular septum in individuals of the mesomorphic body type with a normal body mass index according to echocardiography and to assess the presence or absence of a relationship of these parameters with the gender and age of the subjects. Material and methods. The analysis of the protocols of ultrasound examination of the heart of 202 conditionally healthy persons of adolescence, the first and second periods of adulthood of the mesomorphic body type with a body mass index of 18.5–24.99 kg/m² was carried out. They have no pulmonary and cardiac pathology and risks of cardiovascular diseases. All subjects were divided into three age groups according to the age periodization of human ontogenesis (Moscow, 1965). Echocardiography was performed using a scanner Aloka ProSound Alpha 6. Results. The thicknesses of the anterior wall of the right ventricle, the posterior wall of the left ventricle, and the interventricular septum in women of the second period of adulthood is greater, than in young girl and women of the first period of adulthood (p ˂ 0.05); the thickness of the interventricular septum in men of the second period of adulthood is greater, than in young men and men of the first period of adulthood (p ˂ 0.05). It has been established that the thickness of the anterior wall of the right ventricle and interventricular septum depends on person gender: it is greater in men. In women, moderate correlation was found between the thickness of both the left ventricle (r = 0.425; p < 0.001) and the right (r = 0.411; p < 0.001) with age. A direct relationship (moderate strength) of the thickness of the interventricular septum with age (r = 0.331; p = 0.014) was found in men. Conclusion. The results of this morphological study supplement the information available in the scientific literature on the thickness of the ventricles of the heart and interventricular septum in a conditionally healthy person of the mesomorphic body type with a normal body mass index.